2014
DOI: 10.1007/s11434-014-0246-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of probe lift-up height on CNT electrical properties measurement under EFM DC mode

Abstract: Nowadays, one of the bottlenecks which hinder the development and application of carbon nanotube (CNT) nano device is that no pure semiconducting CNT (s-CNT) or metallic CNT (m-CNT) can be obtained, and for solving this problem scientists proposed some methods on preparation or separation, but all the results still should be detected and feedback to the process for further improving the preparation and separation methods. Thus, it is very important to measure and distinguish the electrical properties of CNT. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…It decreased rapidly to 0.08 • when the lift height increased to 150 nm. By plotting the EFM phase shift as a function of the lift height, it can be observed that the phase shift of the MoS 2 nanosheets with different stacking domains decreased exponentially as the lift height increased (Figure S5 in SI), a result which aligns with the standard EFM response [70][71][72][73].…”
Section: Resultssupporting
confidence: 64%
“…It decreased rapidly to 0.08 • when the lift height increased to 150 nm. By plotting the EFM phase shift as a function of the lift height, it can be observed that the phase shift of the MoS 2 nanosheets with different stacking domains decreased exponentially as the lift height increased (Figure S5 in SI), a result which aligns with the standard EFM response [70][71][72][73].…”
Section: Resultssupporting
confidence: 64%